2022
DOI: 10.7759/cureus.33095
|View full text |Cite
|
Sign up to set email alerts
|

Central Versus Peripheral Invasive Arterial Blood Pressure Monitoring in Liver Transplant Surgery

Abstract: IntroductionInvasive blood pressure monitoring is essential in liver transplant surgery due to expected major hemodynamic shifts. The use of central versus peripheral arterial access, however, is institution-dependent, which can affect clinical decisions regarding vasopressor therapy. Although there are studies that demonstrate inconsistencies based on arterial cannulation sites, few studies have compared femoral and radial artery blood pressures in patients undergoing liver transplant surgery. To our knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The invasive blood pressure (IBP) is the clinical reference method for arterial blood pressure (ABP) monitoring providing accurate beat-to-beat monitoring and is the standard of care in liver transplantation [12,18,34,35,105,116]. The ABP values vary according to the artery monitored [12,18,105,117]. The ABP can be divided into central and peripheral ABPs with the femoral and brachial the…”
Section: Arterial Blood Pressure Monitoringmentioning
confidence: 99%
See 4 more Smart Citations
“…The invasive blood pressure (IBP) is the clinical reference method for arterial blood pressure (ABP) monitoring providing accurate beat-to-beat monitoring and is the standard of care in liver transplantation [12,18,34,35,105,116]. The ABP values vary according to the artery monitored [12,18,105,117]. The ABP can be divided into central and peripheral ABPs with the femoral and brachial the…”
Section: Arterial Blood Pressure Monitoringmentioning
confidence: 99%
“…The radial systolic blood pressure (SBP) is typically higher than the aortic SBP due to peripheral wave reflection, however, this relationship is reversed in critically ill patients including liver transplantation patients [12,34,35,105]. The radial SBP underestimates the central (femoral) SBP during all stages of liver transplantation and that is most pronounced immediately after reperfusion [12,115]. One study showed that the incidence of PRS was 80% when the radial ABP was monitored versus 50% when the femoral ABP or the noninvasive blood pressure (NIBP) were monitored [115].…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations